PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX UPTD SMPN 2 KECAMATAN MUNGKA - Monica, Monica (Departemen Matematika, 2024)
Mathematical problem-solving ability is one of the goals of mathematics education. All students must be able to perform this basic skill. However, students of grade VIII of UPTD SMPN 2 Mungka Regency are still considered to have inadequate mathematical problem-solving abilities. This is evidenced by the results of the initial assessment of the mathematical problem-solving abilities of grade VIII students of UPTD SMPN 2 Mungka Regency. The use of the Problem-Based Learning Model is one way to help students become more proficient in solving mathematical puzzles. This study aims to determine whether the use of a problem-based learning approach affects students' abilities in solving mathematical puzzles. With a posttest-only control design, this study used a quasi-experimental methodology. Grade IX students of UPTD SMPN 2 Mungka Regency became the research population, while grades IX/1 and IX/2 became the research samples. Essay questions about mathematical problem-solving abilities were used as a research technique. A P value of 0.001 was obtained from data analysis using the t-test. Because the P value is less than α = 0.05, H0 is rejected. Thus, it can be said that grade IX students of UPTD SMPN 2 Mungka Regency who study using the Problem Based Learning model are more proficient in solving mathematical puzzles than those who study using the Direct Learning model.Keywords– Problem Based Learning, Mathematical Problem-Solving Skills, Direct Instruction